Clinical Features, Treatment, and Outcome of Psittacosis Pneumonia: A Multicenter Study. (17th February 2023) - Ni, Yueyan; Zhong, Huanhuan; Gu, Yu; Liu, Li; Zhang, Qiang; Wang, Li; Wan, Bing; Chen, Shi; Cao, Min; Xu, Jin; Chen, Cheng; Chen, Yanbin; et al.
Abstract: Background: We aimed to describe psittacosis pneumonia and risk factors for developing severe pneumonia in this multicenter clinical study. Methods: We collected the data of psittacosis pneumonia cases diagnosed with metagenomic next-generation sequencing (mNGS) assay from April 2018 to April 2022 in 15 tertiary hospitals in China. Results: A total of 122 patients were enrolled; 50.0% had a definite history of bird exposure. In 81.2% of cases, onset happened in autumn or winter. The common symptoms were fever (99.2%), cough (63.1%), fatigue (52.5%), shortness of breath (50.0%), chills (37.7%), central nervous system symptoms (36.9%), myalgia (29.5%), and gastrointestinal tract symptoms (15.6%). Laboratory tests showed that >70% of cases had elevated C-reactive protein, procalcitonin, erythrocyte sedimentation rate, D-dimer, lactate dehydrogenase, and aspartate aminotransferase, and >50% had hyponatremia and hypoproteinemia. The most common imaging finding was consolidation (71.3%), and 42.6% of cases met the criteria for severe pneumonia. Age >65 years and male sex were the risk factors for severe pneumonia. The effective proportion of patients treated with tetracyclines was higher than that of fluoroquinolones (66/69 [95.7%] vs 18/58 [31.0%]; P < .001), and the median defervescence time was shorter. After medication adjustment when the diagnosis was clarified, 119 of 122 (97.5%) patients were finally cured and the other 3 (2.5%) died. Conclusions: Psittacosis pneumonia has a high rate of severe disease. Proven diagnosis could be rapidly confirmed by mNGS. Tetracycline therapy had a rapid effect and a high cure rate. Abstract : Psittacosis pneumonia has a high proportion of severe pneumonia. Suspected diagnosis can be derived based on the patient's clinical features and proven diagnosis could be rapidly confirmed by metagenomic next-generation sequencing. Tetracycline therapy had a high cure rate.